2022
DOI: 10.3389/fimmu.2022.886044
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Mast Cell Response to Mycobacterium tuberculosis

Abstract: The immunologic mechanisms that contribute to the response to Mycobacterium tuberculosis infection still represent a challenge in the clinical management and scientific understanding of tuberculosis disease. In this scenario, the role of the different cells involved in the host response, either in terms of innate or adaptive immunity, remains key for defeating this disease. Among this coordinated cell response, mast cells remain key for defeating tuberculosis infection and disease. Together with its effector’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 78 publications
1
3
0
Order By: Relevance
“…The GO and KEGG enrichment analysis revealed enrichment of immune response, which played an important role in TB occurrence and progression. Immune cell infiltration analysis demonstrated that memory B cells, Monocytes, Macrophages M0 and mast cells resting had a higher proportion in TB samples, which was consistent with previous studies 33–36 . This was further validated by scRNA analysis.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The GO and KEGG enrichment analysis revealed enrichment of immune response, which played an important role in TB occurrence and progression. Immune cell infiltration analysis demonstrated that memory B cells, Monocytes, Macrophages M0 and mast cells resting had a higher proportion in TB samples, which was consistent with previous studies 33–36 . This was further validated by scRNA analysis.…”
Section: Discussionsupporting
confidence: 89%
“… 41 Mast cells play a critical role in the establishment and perpetuation of the inflammatory response leading to granuloma generation during tuberculosis. 35 All of these provided further evidence of the importance of immunity in the development of TB.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations